Weaving pedagogical identity: voices and experiences of first- semester students at the university of Pamplona (Colombia) (Revista Investigación & praxis en CS Sociales, 2025)
Building Professional Identity in Pedagogy: A Study at the University of PamplonaThis qualitative ethnographic study explored how nine first-semester students (2024) at the University of Pamplona (Colombia) construct their professional identity in pedagogy. The descriptive research aimed to understand their initial perceptions, expectations, and challenges on the path to teaching, within the institution's cultural and academic environment.Detailed narratives and observations were collected through semi-structured interviews, field diaries, and participant observation. The findings indicate that the emerging professional identity is influenced by prior experiences, intrinsic motivations, and immersion in the university culture. Vocation, empathy, and the desire to transform emerged as fundamental pillars, shaped by the expectations of the environment.The study concludes that educational institutions should foster critical reflection and the development of a teaching identity rooted in humanist and ethical principles, validating individual trajectories and strengthening a sense of belonging from the beginning of their training.
Keywords: Professional identity; pedagogy; qualitative case study; ethnography; humanized approach; teacher education